Developing English Job Interview Skill by Self-Access Language Learning through Audio Podcast-Based Learning Media - Aloysius Soerjowardhana; Raden Arief Nugroho (Soegijapranata Catholic University, 2017)
In the era of ASEAN Economic Community (AEC), Indonesian job seekers must have English competency. Without mastering English language, they will be defeated by foreign ready-to-use job seekers. It can be detected in the job interview that their English competency is low. It is caused by a serious condition that they have no effective time to learn English in formal or non-formal English schools. Hence, an effort to improve their English speaking skill is needed. One of the ways to improve English speaking skill is by Self-Access Language Learning (SALL) through audio podcast-based learning media. By using audio podcast-based learning media, the job seekers can practice their English speaking ability by themselves anytime and anywhere. This research conducted an action research to investigate the improvement of English job interview skill of an interviewee with intermediate level of English, which was focused on the improvement of the interviewee abilities to answer the interviewer’s questions. To assess the quality of the English job interview, the researchers used an interview quality parameter designed by Overseas Programming and Training Support (OPATS) Peace Corps (2005). It is based on the assessment of function and content. The result shows that after two treatments, the job seeker (interviewee) improves her English job interview skill. The improvement can be seen from the changes according to the functional ability; it is shown from the change of answer style from descriptive into narrative way and the changes according to the content; it is shown from the change of answer content from daily routine into professional rational. Therefore, the researchers recommend the Indonesian job seekers to use audio podcast-based learning media by SALL to develop their English job interview skill.